Continuous and Long-Term Measurement of Reticuloruminal pH in Grazing Dairy Cows by an Indwelling and Wireless Data Transmitting Unit. (5th November 2012) - Gasteiner, J.; Guggenberger, T.; Häusler, J.; Steinwidder, A.
Abstract : The aim of the present study was the continuous measurement of ruminal pH in grazing dairy cows to monitor the diets effects on ruminal pH value. A novel indwelling pH-measurement and data transmitting system was given to 6 multiparous cows orally. Ruminal pH was measured every 600 sec over a 40 d period. After barn feeding and changeover to pasture, the following 3 treatments (2 cows/treatment) were included in the measurement period: continuous grazing (G), continuous grazing plus 4 kg/d of hay fed twice daily (GH), and continuous grazing plus 4 kg/d of concentrate (GC). Ruminal pH decreased significantly (P < 0.05 ) from6.58 ± 0.15 to pH6.19 ± 0.19 during feed changeover to pasture. Mean ruminal pH for G, GH, and GC was 6.36, 6.56, and 6.01. Mean 24-h minimum pH was 5.95, 6.20 and, 5.58. The time pH was below 6.3, 6.0, 5.8, and 5.5, for G it was 583, 91, 26, and 3 min/d, for GH it was 97, 12, 0, and 0 min/d and for GC it was 1126, 621, 347, and 101 min/d, respectively. Results were significantly influenced by the diet. The indwelling pH-measurement and data transmitting system is a very useful and proper tool for long-term measurement of ruminal pH in cows.